Public Services at Airmadidi District Office North Minahasa Regency - Arie Supriati; Jan A Rattu; Sjamsi Pasandaran (Jurnal Ad'ministrare, 2020)
The purpose of this study was to assess public service to the public at the Airmadidi district office in North Minahasa Regency by emphasizing the motivation and discipline factors of employees. Research methodology with a qualitative approach establishes data sources on structural, non-structural employees, and the community. Data collection was conducted using interview observation and documentation. The results showed that public services at the Airmadidi district office had run accordingly in terms of covering the performance and responsibilities of employees in public services. However, the quality of work is needed to be improved